Dietary intake, physical activity and sedentary behaviour patterns in a sample with established psychosis and associations with mental health symptomatology. Issue 4 (23rd March 2023) - Martland, Rebecca; Teasdale, Scott; Murray, Robin M.; Gardner-Sood, Poonam; Smith, Shubulade; Ismail, Khalida; Atakan, Zerrin; Greenwood, Kathryn; Stubbs, Brendon; Gaughran, Fiona
Abstract: Background: People with psychosis experience cardiometabolic comorbidities, including metabolic syndrome, coronary heart disease and diabetes. These physical comorbidities have been linked to diet, inactivity and the effects of the illness itself, including disorganisation, impairments in global function and amotivation associated with negative symptoms of schizophrenia or co-morbid depression. Methods: We aimed to describe the dietary intake, physical activity (PA) and sedentary behaviour patterns of a sample of patients with established psychosis participating in the Improving Physical Health and Reducing Substance Use in Severe Mental Illness (IMPaCT) randomised controlled trial, and to explore the relationship between these lifestyle factors and mental health symptomatology. Results: A majority of participants had poor dietary quality, low in fruit and vegetables and high in discretionary foods. Only 29.3% completed ⩾150 min of moderate and/or vigorous activity per week and 72.2% spent ⩾6 h per day sitting. Cross-sectional associations between negative symptoms, global function, and PA and sedentary behaviour were observed. Additionally, those with more negative symptoms receiving IMPaCT therapy had fewer positive changes in PA from baseline to 12-month follow-up than those with fewer negative symptoms at baseline. Conclusion: These results highlight the need for the development of multidisciplinary lifestyle and exercise interventions to target eating habits, PA and sedentary behaviour, and the need for further research on how to adapt lifestyle interventions to baseline mental status. Negative symptoms in particular may reduce patient's responses to lifestyle interventions.